2019
DOI: 10.1039/c9fo00561g
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating NF-κB signaling pathway with triterpenoids for attenuating inflammation:in vitroandin vivostudies

Abstract: Two triterpenoids from Acanthopanax trifoliatus, an edible medicinal plant from Southeast Asia, attenuated lipopolysaccharides-induced inflammation in murine macrophage RAW246.7 cells and tetradecanoylphorbolacetate-induced mouse ear edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Hematoxylin and eosin staining assay was performed on mice ear tissues that were fixed in paraffin and sectioned into 4-µm sections using method previously reported. 8 Immunohistochemical staining assays were performed on mice ear tissue sections as we previously reported. 8 Sectioned tissues were incubated with antimouse monoclonal antibodies including COX-2 and IκB, followed by appropriated secondary antibodies.…”
Section: Histological and Immunohistochemical Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematoxylin and eosin staining assay was performed on mice ear tissues that were fixed in paraffin and sectioned into 4-µm sections using method previously reported. 8 Immunohistochemical staining assays were performed on mice ear tissue sections as we previously reported. 8 Sectioned tissues were incubated with antimouse monoclonal antibodies including COX-2 and IκB, followed by appropriated secondary antibodies.…”
Section: Histological and Immunohistochemical Assaysmentioning
confidence: 99%
“…8 Immunohistochemical staining assays were performed on mice ear tissue sections as we previously reported. 8 Sectioned tissues were incubated with antimouse monoclonal antibodies including COX-2 and IκB, followed by appropriated secondary antibodies. Randomly selected visual fields (n = 10; at 400× magnification) in each group are recorded using a microscopy (AxioScope A1, ZEISS, Germany), and the amount of COX-2 and IκB positive cells were counted with microscopy.…”
Section: Histological and Immunohistochemical Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly cultivated in China, India, Thailand, Vietnam, and the Philippines. Leaves of A. trifoliatus are popularly consumed as vegetables and herbal tea in southern China (Chen et al 2019). Traditionally, A. trifoliatus has also been used as folk medicine to treat various diseases, including lung hemorrhages, bruises, ulcers, and partial (Sithisarn et al 2009).…”
mentioning
confidence: 99%
“…Traditionally, A. trifoliatus has also been used as folk medicine to treat various diseases, including lung hemorrhages, bruises, ulcers, and partial (Sithisarn et al 2009). Pharmacological studies also reported that A. trifoliatus extracts showed numerous biological activities, including antioxidative, anti-inflammatory, anti-cancer, and neuroprotective effects (Chen et al 2019). The sequencing of the chloroplast genome of medicinal plants will promote indepth research on the chloroplast genome of medicinal plants and the development of related industries.…”
mentioning
confidence: 99%